Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
a. 7
b. -18
c. 5
d. 8
e. 5a + 2
f. a² + 4a + 8
Step-by-step explanation:
f(x) = 5x - 3 and g(x) = x² + 2x + 5
for each, we simply plug in what's inside of the parenthesis wherever we see x
f(2) = 5(2) - 3
multiply 5 and 2
f(2) = 10 - 3 = 7
f(-3) = 5(-3) - 3
multiply 5 and -3
f(-3) = -15 - 3 = -18
g(-2) = (-2)² + 2(-2) + 5
evaluate exponent
g(-2) = 4 + 2(-2) + 5
multiply 2 and -2
g(-2) = 4 - 4 + 5 = 5
( the 4's cancel out and we're left with 5 )
g(1) = (1)² + 2(1) + 5
evaluate exponent
g(1) = 1 + 2(1) + 5
multiply 2 and 1
g(1) = 1 + 2 + 5 = 8
f(a+1) = 5(a + 1) - 3
distribute the 5
f(a+1) = 5a + 5 - 3
combine like terms
f(a+1) = 5a + 2
g(a+1) = (a+1)² + 2(a+1) + 5
expand exponent
g(a+1) = (a+1)(a+1) + 2(a+1) + 5
evaluate (a+1)(a+1) using FOIL
g(a+1) = a² + 2a + 1 + 2(a+1) + 5
distribute the 2
g(a+1) = a² + 2a + 1 + 2a + 2 + 5
combine like terms
g(a+1) = a² + 4a + 8
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.